Avifauna pantaneira: diálogo de saberes científico e popular em áreas úmidas (São Pedro de Joselândia, Barão de Melgaço, MT) - Oliveira Júnior, Samuel Borges de (2011)
Presently, the accelerating process of globalization has given a change of values that, unfortunately, affect the daily of Bioregional communities, resulting in both loss of biological diversity as well as cultural diversity of those communities. Thus, this study aims to reveal that the Pantanal s community of São Pedro de Joselândia still has a strong relationship with the environment to which it is inserted, as evidenced by the local culture and resident s knowledge, especially the knowledge about local avifauna, demonstrating also that such knowledge can assist in preparing of bird s inventories made by the scientific community and assist in the recognition of resident s knowledge about the Pantanal wetlands, in relevance of dialogue between local and universal knowledge. The methodology is anchored in the Bioregionalism s theories, which advocate the development of the environment surrounding Bioregional communities, taking into consideration the circumstances and the knowledge of these communities. The results allowed the construction of a local list with 162 species of birds belonging to 56 families. The identifications made by the residents were made visually or by vocalizations of the species, and the classification made in the community is linked to morphology, behavior or vocalization of the species. Furthermore, we identified the ecosystem services of provision related to species that serve as a food supplement for the community, and cultural, related to species with some symbolic relation to the residents. Finally, an educational booklet about the community of São Pedro was produced, together with community residents, showing a bit of everyday life and relationships that residents have with the wetland environment, serving as a return to the community of the results achieved during the research.